2001
DOI: 10.1074/jbc.m102356200
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Substrate Specificity of Human Mast Cell Tryptase βI and Demonstration of Its Importance in Bacterial Infections of the Lung

Abstract: Human pulmonary mast cells (MCs) express tryptases ␣ and ␤I, and both granule serine proteases are exocytosed during inflammatory events. Recombinant forms of these tryptases were generated for the first time to evaluate their substrate specificities at the biochemical level and then to address their physiologic roles in pulmonary inflammation. Analysis of a tryptase-specific, phage display peptide library revealed that tryptase ␤I prefers to cleave peptides with 1 or more Pro residues flanked by 2 positively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
134
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(139 citation statements)
references
References 71 publications
3
134
0
2
Order By: Relevance
“…Other enzymes, such as proteases, are known to exert microbicidal effects through cytokine production (42)(43)(44). Our findings in this study imply that proteases may not be the primary antimicrobial component in mast cells.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Other enzymes, such as proteases, are known to exert microbicidal effects through cytokine production (42)(43)(44). Our findings in this study imply that proteases may not be the primary antimicrobial component in mast cells.…”
Section: Discussionmentioning
confidence: 48%
“…For instance, mast cells sense the type 1 fimbriae of E. coli through surface-expressed CD48, resulting in release of the potent neutrophil chemoattractant TNF-a in a process that is pivotal for elimination of the bacteria (42). Additionally, mast cell tryptase b I reportedly plays a central role in the host defenses of the lung by recruiting neutrophils (43), and cecal ligation and puncture models demonstrated that mast cell chymase is essential for survival in cases of septic peritonitis (44). We revealed in the present study, to our knowledge for the first time, that although reconstitution of W/W v mice with BL/6-BMMCs reduced the lethality of S. epidermidis infection, grafting of hexb 2/2 -BMMCs did not reduce mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the hyperalgesic effects of tryptase in the skin are diminished in PAR2ko mice (33). A recent report has questioned the capacity of tryptase to activate PAR2 (44). The explanation of this discrepancy is unknown.…”
Section: Tryptase and Trypsin May Activate Par2 In The Inflamed Airwaymentioning
confidence: 90%
“…Thus, the mechanism(s) by which mMCP-6 and mMCP-7 control the severity of the arthritis in mBSA/IL-1␤-treated C57BL/6 mice at the molecular level remain to be determined. Mouse MCP-7 is able to induce the recruitment of eosinophils into the peritoneal cavity (42) and neutrophils and eosinophils in the conjunctiva by activating an IL-6-dependent pathway that eventually leads to the generation of other cytokines and chemokines (Miyazaki D, et al: unpublished observations). Mouse MCP-6 and its human homolog hTryptase-␤1 induce neutrophil recruitment when injected into the mouse lung or peritoneal cavity (41,46).…”
Section: Mc-deficientmentioning
confidence: 99%